300. Computed tomography use in a large italian region: Trend analysis 2004–2014 of emergency and outpatient CT examinations in children and adults. (December 2018) - Torresin, A.; Pola, A.; Corbella, D.; Righini, A.; Colombo, P.E.; Vismara, L.; Trombetta, L.; Maddalo, M.; Introini, M.V.; Tinelli, D.; Strohmenger, L.; Garattini, G.; et al.
Abstract : Purpose: To analyse Computed Tomography (CT) use in recent years in a high population density area in Italy (approximately 10 million inhabitants, including 1 million children), focusing on the developing age. Methods: Retrospective analysis of records from the Health Care IT System, covering more than 400 hospitals and clinics. Description of CT use between 2004 and 2014 in emergency and outpatient care and assessment of the radiation exposure trend. Results: Over 9 million scans were performed. Emergency procedures showed a global increase of 230%, which mainly consisted of Head exams. In the global outpatient setting, the annual number of CT scans per person increased approximately 19%. A moderate increase in CT exams was observed in the developing age population, while a remarkable increase in Dental, Chest and Abdominal procedures occurred within the 10–30-year age range. The increase in the mean annual dose per caput in the global patient pool was approximately 42%, increasing from 0.72 mSv to 1.03 mSv. The population rate that received an annual radiation dose per caput from CT higher than 1 mSv tripled in the 11-year interval, increasing from 16 to 48%. Conclusions: The outcomes raise a special concern for teenagers and young adults, taking into account that the widespread use of CT represents probably the single most important achievement in diagnostic radiology.